(untitled) (World Bulletin of Social Sciences, 2024)
This article talks about the influence of the era of slavery on the periodic evolution of folk proverbs. The period of creation of folk proverbs can be recognized by the images in them. Usually in the periodic evolution of proverbs, the evolution of content is ahead of form. The content of proverbs quickly adapts to the new era. The form of the proverb remains normal, but the images become symbolic. Determining which period a proverb belongs to based on its images is discussed in this article using the example of the period of slavery.